DNA Aptamers for the Characterization of Histological Structure of Lung Adenocarcinoma - Galina S. Zamay; Tatiana I. Ivanchenko; Tatiana N. Zamay; Valentina L. Grigorieva; Yury E. Glazyrin; Olga S. Kolovskaya; Irina V. Garanzha; Andrey A. Barinov; Alexey V. Krat; Gleb G. Mironov; Ana Gargaun; Dmitry V. Veprintsev; et al. (Elsevier, 2017)
Nucleic acid aptamers are becoming popular as molecular probes for identification and imaging pathology and, at the same time, as a convenient platform for targeted therapy. Recent studies have shown that aptamers may be effectively used for tumor characterization and as commercially available monoclonal antibodies. Here we present three DNA aptamers binding to whole transformed lung cancer tissues, including tumor cells, connective tissues, and blood vessels. Protein targets have been revealed using affinity purification followed by mass spectrometry analyses, and they have been validated using a panel of correspondent antibodies and 3D imaging of tumor tissues. Each of the proteins targeted by the aptamers is involved in cancer progression and most of them are crucial for lung adenocarcinoma. We propose the use of these aptamers in aptahistochemistry for the characterization of the histological structure of lung adenocarcinoma. The value of the presented aptamers is their application together or separately for indicating the spread of neoplastic transformation, for complex differential diagnostics, and for targeted therapy of the tumor itself as well as all transformed structures of the adjacent tissues. Moreover, it has been demonstrated that these aptamers could be used for intraoperative tumor visualization and margin assessment. Keywords: DNA-aptamer, lung adenocarcinoma, histological structure